Of Grasshoppers, Caterpillars, and Beans: A Historical Perspective on Hmong Messianism. Issue 2 (July 2015) - Tapp, Nicholas
Abstract: This paper considers Hmong messianism in Asia and beyond from a historical perspective, arguing that its thematic repetition of themes and ideas requires a new understanding of subjectivity at the intersections of the psychological with the social and political. Hmong messianic movements have adopted a variety of forms ranging from the more indigenous to the more explicitly Christian. While the attempt is not to seek a particularist 'ethnographic-historical' understanding of these recurrent movements, nevertheless the contexts of colonialisation, mass migration and marginal social status are suggested as providing the essential background for such an understanding. Several different theoretical approaches to understanding such movements are considered, with some attention to major theorists of structure and agency. It is argued that ultimately messianic movements can be appreciated in terms of a kind of 'anticipatory consciousness', and are enabled to challenge current social orders because they are motivated by a particular notion of time, which combines a medieval and revolutionary notion of simultaneity with one of historical progression which is, however, not gradualist. A 'central irreducible core' of ritual beliefs and actions among the Hmong emerges from this consideration of historical movements, which may demand a reconsideration of older and largely abandoned notions of cultural structure.